Supplemental Cellular Protection by a Carotenoid Extends Lifespan via Ins/IGF-1 Signaling in Caenorhabditis elegans. (12th October 2011) - Yazaki, Koumei; Yoshikoshi, Chinatsu; Oshiro, Satoru; Yanase, Sumino
Abstract : Astaxanthin (AX), which is produced by some marine animals, is a type of carotenoid that has antioxidative properties. In this study, we initially examined the effects of AX on the aging of a model organism C. elegans that has the conserved intracellular pathways related to mammalian longevity. The continuous treatments with AX (0.1 to 1 mM) from both the prereproductive and young adult stages extended the mean lifespans by about 16–30% in the wild-type and long-lived mutant age-1 of C. elegans . In contrast, the AX-dependent lifespan extension was not observed even in a daf-16 null mutant. Especially, the expression of genes encoding superoxide dismutases and catalases increased in two weeks after hatching, and the DAF-16 protein was translocated to the nucleus in the AX-exposed wild type. These results suggest that AX protects the cell organelle mitochondria and nucleus of the nematode, resulting in a lifespan extension via an Ins/IGF-1 signaling pathway during normal aging, at least in part.